Epidemiological analysis of accidents by scorpions in a municipality in the Triângulo Mineiro - Motta, Ana Laíza Ferreira; Arruda , Anna Myrian Vieira; Melo, Guilherme Cerva de; Oliveira , Stefan Vilges de (Medicina (Ribeirao Preto), 2022)
Introduction: Minas Gerais is the Brazilian state with the highest rate of scorpionism, 223,033 cases were recorded between 2010-2017, so reflections on how to reduce this public health problem are necessary. Objective: to describe the epidemiological profile of accidents with scorpions that occurred in the municipality of Patos de Minas (MG), from 2013 to 2017, and to develop an intervention project based on it. Methods: First, the number of accidents by venomous animals in Patos de Minas (MG) was analyzed using the variables included in the SINAN notification and investigation form, available on DATASUS. Additionally, two databases, CAFE and Pubmed, were used for the theoretical framework, with the following descriptors: “escorpião”, “Minas Gerais”, “envenenamento”, “prevenção”, and their respective translations into English: “scorpion”, “Minas Gerais”, “envenomation” and “prevention”. Results: Scorpion sting accidents were the most recorded among venomous animals, and were increased annually during the study period, reaching, in 2017, the number of 274 reported cases. In addition, the frequency of accidents was recorded in greater numbers in males (51.18%) and the most affected age group was between 20 and 39 years of age (32.64%). It is also observed that most of the victims were classified as mild cases and treated in the first hour of the sting (97.92%), with no deaths in the period. The results found are in agreement with the references used, being more common, in studies, the registration of mild cases, in male adults. For the basis of the intervention proposal, five articles were used, and based on them, preventive, corrective environmental and educational actions are proposed. Conclusion: The study allowed to identify the target audience of the intervention proposals and when they should be intensified, to try to contain, thus, the constant increase in cases of scorpionism in the analyzed municipality.